How to Achieve National Goals in the European Union? Small State Strategy in Internal Security Integration - Ramon Loik; Ketlin Jaani-Vihalem (Romanian Journal of European Affairs)
The Treaty of Lisbon brought about principal changes in the decision-making process of the European Union by forcing to abjure the intergovernmental approach and increasing the competencies of supranational institutions. Every member state in the EU has its national goals and preferences. Due to limited resources, the small Member States need to develop their strategies in certain ways for successful navigation between the institutions and regulatory frames, domestic factors and interests of other actors. The paper discusses on the bases of explanatory case studies that small states’ efficiency in the process of EU internal security integration is mainly influenced by (i) coherent domestic political consensus, (ii) clear setting of strategic priorities and their multi-level use, (iii) professionalism and expertise of civil servants involved, (iv) appropriate timing and flexible negotiation skills to represent its interests.